2021
DOI: 10.3390/ijms22147262
|View full text |Cite
|
Sign up to set email alerts
|

Increased Endocytosis of Cadmium-Metallothionein through the 24p3 Receptor in an In Vivo Model with Reduced Proximal Tubular Activity

Abstract: Background: The proximal tubule (PT) is the major target of cadmium (Cd2+) nephrotoxicity. Current dogma postulates that Cd2+ complexed to metallothionein (MT) (CdMT) is taken up through receptor-mediated endocytosis (RME) via the PT receptor megalin:cubilin, which is the predominant pathway for reuptake of filtered proteins in the kidney. Nevertheless, there is evidence that the distal parts of the nephron are also sensitive to damage induced by Cd2+. In rodent kidneys, another receptor for protein endocytosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…MT protein has also been reported to provide a protective response against Cd in the body, so increased expression is the body's response to decrease Cd toxicity. [38] A biochemical study was performed to check the functions of significant fluctuation in all groups. High creatinine levels were observed in Cd treated group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MT protein has also been reported to provide a protective response against Cd in the body, so increased expression is the body's response to decrease Cd toxicity. [38] A biochemical study was performed to check the functions of significant fluctuation in all groups. High creatinine levels were observed in Cd treated group.…”
Section: Discussionmentioning
confidence: 99%
“…MT protein has also been reported to provide a protective response against Cd in the body, so increased expression is the body's response to decrease Cd toxicity. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…Elimination of cadmium by the kidneys is slow. Chronic exposures to cadmium ions can result in proteinuria and tubular dysfunction in the proximal tubules ( Davenport, 2020 ; Godt et al, 2006 ; Yan & Allen, 2021 ; Zavala-Guevara et al, 2021 ). Renal toxicity from cadmium exposure is correlated with the number of cadmium ions in kidney tubule cells, reabsorption, degradation of cadmium metallothionein complexes, and excess production of metallothionein by renal tubules ( Davenport, 2020 ; Zavala-Guevara et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposures to cadmium ions can result in proteinuria and tubular dysfunction in the proximal tubules ( Davenport, 2020 ; Godt et al, 2006 ; Yan & Allen, 2021 ; Zavala-Guevara et al, 2021 ). Renal toxicity from cadmium exposure is correlated with the number of cadmium ions in kidney tubule cells, reabsorption, degradation of cadmium metallothionein complexes, and excess production of metallothionein by renal tubules ( Davenport, 2020 ; Zavala-Guevara et al, 2021 ). Cadmium toxicity observed in the renal cortex of laboratory rats ( Rattus rattus ) resulted in cytosolic damage and renal malfunction after oral administration of cadmium chloride (CdCl 2 ) ( Alimba et al, 2021 ; Hashim et al, 2018 ; Siddiqui, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…A question remains with regard to the specificity of this cadmium effect. A recent study suggested that reabsorption of β 2 MG and MT may occur mainly at the distal tubule and collecting duct, where other receptor-mediated endocytosis systems are expressed [ 20 ].…”
mentioning
confidence: 99%